GRETL 2019. Proceedings of the International Conference on the Gnu Regression, Econometrics and Time-series Library - Riccardo Lucchetti (Scuola delle Scienze Umane e Sociali. Quaderni, 2019)
This book collects the papers presented at the 6th Gretl Conference, which took place at the Dipartimento di Scienze Politiche, University of Naples, on 13th-14th of June, 2019. The papers (which had been selected through a refereeing process) contain theoretical topics on computational problems as well as empirical applications using the program, and cover a wide range of topics in statistics and applied econometrics, among which Generalized Dynamic Factor Models, Propensity Score Matching, Bayesian Model Averaging, Spatial Models, Cointegration and Boostrap Techniques.